Exploring ocean literacy at the French Mediterranean coast: Information seeking, knowledge, awareness and concern about threats among residents and visitors in Port-Cros National Park - Demmler, Rebecca A.; Kleemann, Susanne (ERDKUNDE, 2025)
The Mediterranean Sea is one of the world’s most biologically diverse yet ecologically threatened marine ecosystems. In response to increasing environmental pressures, marine protected areas such as Port-Cros National Park in France play a crucial role in conservation efforts. However, effective marine protection requires more than legal frameworks. It demands an ocean-literate public that understands the interconnectedness of marine ecosystems and human activities, and has the capacity to engage in conservation efforts. This study investigates ocean literacy among 405 residents and visitors to Port-Cros National Park, with a particular focus on information seeking, knowledge of marine issues, and awareness and concern about environmental threats. Results indicate high awareness and concern about marine pollution but only moderate active information seeking, knowledge of ecological conditions and species population trends. Plastic and oil pollution were most frequently noted, with online sources as the primary information channel. Although residents reported more proactive information seeking and higher awareness of pollution, concern and knowledge levels were similar across residency groups, with visitors even demonstrating a better understanding of declining fish populations. The findings underscore the importance of place-based marine education initiatives that address passive information acquisition and knowledge gaps while leveraging existing emotional connections to the marine environment. Accessible, solution-oriented communication strategies that convey the full range of ecological threats seem essential to strengthen regional ocean literacy and promote sustained, informed engagement with marine ecosystems in Port-Cros National Park.